2022
DOI: 10.1186/s12950-022-00308-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent evidence from omic analysis for redox signalling and mitochondrial oxidative stress in COPD

Abstract: COPD is driven by exogenous and endogenous oxidative stress derived from inhaled cigarette smoke, air pollution and reactive oxygen species from dysregulated mitochondria in activated inflammatory cells within the airway and lung. This is compounded by the loss in antioxidant defences including FOXO and NRF2 and other antioxidant transcription factors together with various key enzymes that attenuate oxidant effects. Oxidative stress enhances inflammation; airway remodelling including fibrosis and emphysema; po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 112 publications
0
23
0
Order By: Relevance
“…In the airways, the lungs and blood of COPD patients show mitochondrial morphological alterations, mitochondrial dysfunction, and increased ROS levels. 393 The mitochondriaspecific antioxidant mitoQ can reduce airway smooth muscle cell inflammation and the airway response. 394 Mitochondrial autophagy is also deficient in COPD patients.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…In the airways, the lungs and blood of COPD patients show mitochondrial morphological alterations, mitochondrial dysfunction, and increased ROS levels. 393 The mitochondriaspecific antioxidant mitoQ can reduce airway smooth muscle cell inflammation and the airway response. 394 Mitochondrial autophagy is also deficient in COPD patients.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of mortality worldwide ( 1 ). Oxidative stress (OS) is one of the most important factors contributing to the pathogenesis and severity of COPD ( 2 , 3 ). COPD is a heterogeneous disease with several potentially treatable traits that have been associated with disease prognosis ( 4 ) including muscle weakness ( 5 ), reduced exercise capacity ( 6 ), and increased oxygen desaturation (OD) during exercise ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both FoxO and TGF-β have been linked to cancer pathogenesis, with the former being a positive mediator of cell growth (77) and vascular remodeling (41) and the latter having both tumor suppressing and promoting functions (78). Studies have shown decreased levels of the FoxO protein in COPD (41, 79-81). Di Stefano et al found that, compared to controls, COPD peripheral airway samples have decreased TGF-β1 + and TGF-β3 + bronchial epithelial cells (82).…”
Section: Discussionmentioning
confidence: 99%